The performance of forecast-based monetary policy rules under model uncertainty - John C. Williams; Andrew T. Levin; Volker Wieland (European Central Bank (ECB), 2001)
We investigate the performance of forecast-based monetary policy rules using five macroeconomic models that reflect a wide range of views on aggregate dynamics. We identify the key characteristics of rules that are robust to model uncertainty: such rules respond to the one-year ahead inflation forecast and to the current output gap, and incorporate a substantial degree of policy inertia. In contrast, rules with longer forecast horizons are less robust and are prone to generating indeterminacy. In light of these results, we identify a robust benchmark rule that performs very well in all five models over a wide range of policy preferences
Keywords: E31; E52; E58; E61; 330